Estudio de la cámara magmática principal del volcán Sumaco mediante tomografía sísmica - Guamán Viveros, Anderson Isaac (2020)
The back-arc (Eastern sub-Andean belt) of the Ecuadorian Andes encompass four volcanoes: Reventador, Yanaurco, Pan de Azúcar, and Sumaco. Despite the proximity of these volcanoes, Sumaco volcanic materials are distinctly SiO2-undersaturated alkalines. Through seismic travel time tomography, three velocity models (, ∆, / ) were generated to identify the primary magmatic reservoir of the Ecuadorian back-arc. The inverse problem was solved using the INSIGHT computer code package in a gridded parallelepiped box with a cell size of 5 km in the horizontal direction and 2 km in the vertical direction. This study finds the principal magmatic chamber located below the Sumaco volcano but slightly shared with the extinct Pan de Azúcar and Yanaurco volcanoes. Sumaco Fault extension is also recognizable and is expected to be responsible for the rapid ascent of the magma towards the surface before an eruption. As a conclusion, a significant factor that could lead to the differentiation of the Sumaco lavas is a hypothetical flat slab block below the volcano